A Multi-institutional Assessment of Causes, Reoperation Rates, and Mortality in Forearm Acute Compartment Syndrome - Ciara A. Brown, MD; Ambika Menon, MD; Hannah E. Jones, MD; Paul A. Ghareeb, MD (Plastic and Reconstructive Surgery, Global Open)
Background:. Forearm acute compartment syndrome (ACS) requires emergent fasciotomy to avoid irreversible sequelae. Although trauma is the most common cause of ACS, atraumatic causes require a high index of suspicion. We evaluated scenarios and outcomes of forearm fasciotomies to better understand this rare but critical diagnosis. Methods:. All patients who underwent forearm fasciotomy at 2 institutions were retrospectively reviewed from 2007 to 2022. Clinical outcomes including mortality, secondary surgery, and complications were analyzed. Results:. Eighty-eight forearm fasciotomies were performed during the study period. The most common clinical scenarios for fasciotomy were trauma (48%) and arterial catheterization (13.6%). Forty-two percent of patients underwent skin closure at the index operation without complication. The reoperation rate following fasciotomy was 55% (n = 48), all of which occurred in the secondary closure cohort. The overall mortality rate after forearm fasciotomy was 13.7% (23% in atraumatic versus 8% in traumatic causes, P = 0.09). Atraumatic causes were found to have significantly increased underlying medical comorbidities compared to traumatic causes (P < 0.05). Increased lactate and potassium were associated with mortality across all groups. Conclusions:. Forearm ACS should be acknowledged as a potential risk of arterial catheterization procedures. The risk of mortality after fasciotomy is high, and forearm ACS in highly comorbid individuals may be considered a surrogate marker of underlying medical disease severity. The risk of subsequent mortality in these cases should be used to counsel patients. Primary closure of fasciotomy sites in appropriately selected cases can safely reduce the number of secondary procedures.